Empowerment Level of MSMEs in Local Food Processing Industry in Kuningan Regency, West Java - Nia Nurohmiasih; Siwi Gayatri; Bambang Dwiloka (Green Publisher Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital to Indonesia's economy, significantly aiding job creation and economic growth while enhancing community welfare. In Kuningan Regency, known for its agricultural strengths and superior food crops like sweet potatoes and cassava, there is substantial potential for MSME development in local food processing. However, the post-pandemic landscape has seen a decline in MSMEs, facing challenges such as limited capital, competitiveness, and human resources. This study investigates the empowerment levels of MSME food processors in Kuningan Regency and their impact on productivity. Data were collected through interviews with 114 respondents from Kramatmulya, Cigugur, and Kuningan Districts. Utilizing the Likert Scale and SPSS for statistical testing, the research reveals that MSMEs in the food processing sector are categorized as empowered and moderately empowered. Regression analysis indicates that all independent variables—input, output, and marketing—positively and significantly influence productivity, with significance values below 0.05. The findings suggest that untapped resources and market potential could enhance productivity. This study aims to inform more effective empowerment policies to bolster MSMEs in Kuningan Regency, improving their competitiveness in a challenging market.